Implementation Of Just-In-Time (Jit) In Inventory Management: A Case Study In A Manufacturing Company - Tuti Susanti; Rionaldi Rionaldi; Dhani Aristiawan; Hidayattul Taufid; Lusiana Lusiana (Eduvest - Journal of Universal Studies, 2025)
Just-In-Time (JIT) is an inventory management strategy that aims to reduce waste and increase efficiency in the production process. In the context of manufacturing companies, the implementation of JIT offers significant advantages, such as reduced inventory costs and improved product quality. However, the implementation of JIT also faces challenges, including dependence on suppliers and fluctuations in demand. This article not only discusses the benefits and challenges of JIT, but also presents case studies of several companies that have successfully implemented this concept. By highlighting best practices and risk mitigation strategies, it is hoped that this research can provide deeper insights into the application of JIT in inventory management, as well as encourage companies to adopt a more responsive and efficient approach in their operations.